Hypertelorism-microtia-clefting syndrome in a 9-month-old child: A rare case report - Supreet Shirolkar; Rajib Sikdar; Khooshbu Gayen; Anisha Bag; Santanu Mukhopadhyay; Subir Sarkar (Wolters Kluwer Medknow Publications, 2022)
Hypertelorism-microtia-clefting (HMC) syndrome is a very rare autosomal recessive disorder. HMC syndrome is malformation of orofacial region characterized by hypertelorism, microtia, and cleft lip and palate. Additional features such as microcephaly, congenital heart disease, and kidney abnormalities can also be present in HMC syndrome. Only few case reports of this syndrome have been documented in dental literature. In the article, we report a case of 9-month-old girl child presenting with typical features of this syndrome. The rarity of the syndrome prompted us to report the case.